Implementation of the principle of proportionality in the use of the preamble - Тоцький, Броніслав Артурович; Черненко, Зоряна Степанівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2010)
This article analyzes the theoretical and practical problems of the usage of preamble. Role of the preamble is analyzed from the principle of proportionality which is actual at the context of the developing of the rule of law and European integration processes.